The headings of the Psalms in the two Syriac versions of the commentary of Athanasius - Van Rooy, H. F. (Old Testament essays, 2004)
There are two Syriac versions of the commentary of Athanasius on the Psalms, a longer and a shorter one. This study deals with the headings of the Psalms in the two Syriac versions, in comparison with the headings in the original Greek commentary and in the Syro-Hexapla. The summaries at the beginning of the different Psalms are related in a linear fashion. The shorter commentary depends on the longer one and the longer one on a Greek original. The headings in the Greek commentary are those of the Septuagint, with a few variants. Most of these variants agree with variants given in the edition of Rahlfs. The Syriac headings of the shorter commentary are usually in agreement with that of the Syro-Hexapla. Many of the differences between the longer commentary on the one hand and the other two are related to the fact that the longer commentary ascribes all twenty-eight Psalms discussed in this article to David. The headings in the longer commentary are not just translations from a Greek original, but are the work of the translator.